Effect of chemical denture cleansers on flexural resistance and color changes of microwave-polymerized acrylic resins - Helena de Freitas Oliveira Paranhos; Iara Augusta Orsi; Osvaldo Zaniquelli; Maria Cristina Candelas Zuccolotto; Fabrício Magalhães (Universidade Estadual de Campinas, 2008)
Aim: The aim of this study was to assess the flexural resistance and color alterations of microwave-polymerized acrylic resins immersed in denture cleansers for different periods of time. Methods: Forty-five rectangular specimens (65x10x3mm) of each commercial brand of the microwave-activated acrylic resins (Vipi Wave and Onda Cryl) were divided in three denture cleanser groups (Bony Plus, Corega Tabs and Efferdent Plus) and a control group (immersion in water). Soaking trials of 15 min and 8 h simulated 30 days of use. The flexural strength test was carried out in a universal testing machine. Color alterations were assessed by visual inspection of photographs. The results obtained in the flexural test, in kgf, were converted to MPa and these values were submitted to analysis of variance with a 5% significance level. Results: There were no significant differences (p<0.05) between Onda Cryl (85.61±12.76) and Vipi Wave (89.8±19.95) after the soaking trials regarding the use of different denture cleansers. No differences were found in relation to the solutions [Bony Plus (88.52±9.89), Corega Tabs (88.75±12.71) and Efferdent (85.86±12.11)], soaking periods [control (87.17±12.92), 15 min (88.05±11.74) and 8 h (87.91±10.30)], and interactions during the 30 days of simulated use. Visual inspection did not detect any color alterations. Conclusions: Denture cleansers, when used according to the manufacturers' instructions, did not cause any mechanical or visual alterations in the microwave-polymerized acrylic resins after a simulated period of 30 days of use.